If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1(4x + 6) = 24 Reorder the terms: 9x + -1(6 + 4x) = 24 9x + (6 * -1 + 4x * -1) = 24 9x + (-6 + -4x) = 24 Reorder the terms: -6 + 9x + -4x = 24 Combine like terms: 9x + -4x = 5x -6 + 5x = 24 Solving -6 + 5x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 5x = 24 + 6 Combine like terms: -6 + 6 = 0 0 + 5x = 24 + 6 5x = 24 + 6 Combine like terms: 24 + 6 = 30 5x = 30 Divide each side by '5'. x = 6 Simplifying x = 6
| 7+2x(y+3)= | | 5g^8+25g^5-20g^3= | | 16w^3-25w=0 | | N+12=38 | | m=13a-7 | | (14+x)=346 | | (14x^3-18x^2-10x)= | | X+16=19x | | 12x^5-20x^4+16x^2= | | 9r^3-16r=0 | | 4(x+2)=x-1 | | 7(4+2x)(28+14x)=3 | | 5x+3=9x-1 | | -6x-4=1x+66 | | x-5/8=7/8 | | 1.9x-1.3=-3.9 | | v^2=3v | | 0.3y+.55=-0.05 | | 3(5a-15)= | | 2(3x-4)=-4 | | 6x^3-11x^2+6x-1=0 | | 8(3y-6)-(7y+8)= | | x^2-4x-50=0 | | (-2a^4b^4)(8a^3b^3)= | | 346=14+x | | 5-3x-9= | | 11x^2+5x+1=0 | | 4(5x+3)=20x | | 3+3+8(4-2k)+8(4-2k)=9 | | -12u=4u^2+9 | | 3(2U+9)=15 | | 4+x-6+3x=-2+6x |